2005
DOI: 10.1111/j.0022-202x.2005.23894.x
|View full text |Cite
|
Sign up to set email alerts
|

Sunlight-Induced Immunosuppression in Humans Is Initially Because of UVB, Then UVA, Followed by Interactive Effects

Abstract: Solar-simulated ultraviolet radiation (ssUV) suppresses immunity in humans. The ultraviolet B (UVB) waveband is recognized as immunosuppressive; however the relative significance of UVA to ssUV immunosuppression is unknown. We created dose and time-response curves for UVB-, UVA-, and ssUV-induced suppression of memory immunity to nickel in humans. UVB caused immunosuppression within 24 h. UVA immunosuppression required 48 h and was normalized by 72 h. UVB alone accounts for ssUV immunosuppression at 24 h, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 33 publications
2
56
0
Order By: Relevance
“…There seems to be some kind of dose relationship with different effects on different dose levels 47,48 and chronology of effects. 49 UV radiation activates similar immunological pathways to suppress the induction, or the elicitation, of the immune response. 50 As part of extra corporeal photopheresis UV-B modulates immunoresponse and is able to meliorate the clinical course of cutanous T-cell lymphoma.…”
Section: Biological Plausibilitymentioning
confidence: 99%
“…There seems to be some kind of dose relationship with different effects on different dose levels 47,48 and chronology of effects. 49 UV radiation activates similar immunological pathways to suppress the induction, or the elicitation, of the immune response. 50 As part of extra corporeal photopheresis UV-B modulates immunoresponse and is able to meliorate the clinical course of cutanous T-cell lymphoma.…”
Section: Biological Plausibilitymentioning
confidence: 99%
“…1 An important feature of UVB exposure is the suppression of both primary and memory recall immune responses resulting in antigen-specific tolerance. 2 This study examined the cellular mechanisms of systemic UVB-induced immunosuppression, which is a phenomenon that can be observed when one skin site is exposed to UVB but antigen is applied at a distal, unirradiated site.…”
mentioning
confidence: 99%
“…Using a contact allergy model, it has been shown that there is moderate evidence of a positive interaction of UVB and UVA in human immunosuppression (Poon et al, 2005). Based on a human contact allergy model, the optimal wavelengths of the immunosuppressive action by UVB appear to be around 300 nm and for UVA around 370 nm.…”
Section: Immunosuppressionmentioning
confidence: 99%